2020
DOI: 10.1021/acscatal.9b04505
|View full text |Cite
|
Sign up to set email alerts
|

Single Nanometer-Sized NiFe-Layered Double Hydroxides as Anode Catalyst in Anion Exchange Membrane Water Electrolysis Cell with Energy Conversion Efficiency of 74.7% at 1.0 A cm–2

Abstract: We used a liquid phase reaction to synthesize a nickel (Ni) and iron (Fe)-containing layered double hydroxide (NiFe-LDH), having a lateral size less than 10 nm. A chelating agent introduced into the media was thought to increase the concentration of metal hydroxide nuclei and suppress excessive growth of the LDH crystal, resulting in the synthesis of nanometer-sized LDH. The NiFe-LDH catalyzed the oxygen evolution reaction (OER) at an overpotential of 247 mV and current of 10 mA cm–2, which is superior to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 64 publications
1
77
1
2
Order By: Relevance
“…The value of Tafel slope indicated that the NiFe LDH/NF‐IH presented fast OER kinetics. [ 31 ] The EIS Nyquist plots in Figure S11 in the Supporting Information, electrochemically active surface area in Figure S12 in the Supporting Information, and long‐term stability tests in Figure 4f also confirmed that the NiFe LDH/NF‐IH synthesized by IH presented the highly efficient electrocatalytic OER activity. Moreover, after i – t testing, the morphology of NiFe LDH/NF‐IH nanosheets still retained (Figure S13, Supporting Information), showing the outstanding stability in structure.…”
Section: Resultsmentioning
confidence: 64%
“…The value of Tafel slope indicated that the NiFe LDH/NF‐IH presented fast OER kinetics. [ 31 ] The EIS Nyquist plots in Figure S11 in the Supporting Information, electrochemically active surface area in Figure S12 in the Supporting Information, and long‐term stability tests in Figure 4f also confirmed that the NiFe LDH/NF‐IH synthesized by IH presented the highly efficient electrocatalytic OER activity. Moreover, after i – t testing, the morphology of NiFe LDH/NF‐IH nanosheets still retained (Figure S13, Supporting Information), showing the outstanding stability in structure.…”
Section: Resultsmentioning
confidence: 64%
“…[11] A record-low cell voltage of 1.59 V was obtained at 1.0 A cm −2 at 80 °C, but using a noblemetal catalyst for HER, and a non-noble-metal catalyst (NiFe LDH) for OER. [12] Here we report an AEM electrolyzer that operates at 1.57 V for 1.0 A cm −2 at 80 °C, the lowest for any catalytic stability of NiMo-NH 3 /H 2 catalyst was confirmed in a 20 h electrolysis at −0.1 V vs. RHE, where the current density showed negligible change ( Figure S8, Supporting Information).…”
mentioning
confidence: 78%
“…[ 11 ] A record‐low cell voltage of 1.59 V was obtained at 1.0 A cm −2 at 80 °C, but using a noble‐metal catalyst for HER, and a non‐noble‐metal catalyst (NiFe LDH) for OER. [ 12 ] Here we report an AEM electrolyzer that operates at 1.57 V for 1.0 A cm −2 at 80 °C, the lowest for any AEM electrolyzer. Our electrocatalysts are based on the same base material, NiMo oxide.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results with the Sustainion ® -based system were a set of ionomers and membranes that were stable for at least 12,000 h at 60 • C in 1 M KOH, as shown in Figure 2. Presently, these membranes are being evaluated by multiple investigators [21][22][23][24][25][26][27][28][29]. This paper briefly reviews the results in the CO 2 conversion to CO as well as in the conversion to formic acid.…”
Section: Introductionmentioning
confidence: 99%